Processing, storage methods and quality attributes of spices and aromatic herbs in the local merchandising chain in Benin - Akpo-Djènontin, D. O. O; Anihouvi, Victor B.; Vissoh, V. P.; Gbaguidi, A. Fernand; Soumanou, M. (My University, 2016)
This study investigated the processing, the commercialization and the consumption practices of spices and aromatic herbs in different districts of Benin. The investigation was done through a survey using a questionnaire. The questionnaire mainly focused on the socio-cultural profile of actors, the spices and aromatic herbs commercialized, the processing techniques, the quality attributes according to the actors, the forms of consumption and the storage methods. The data collected were analysed using descriptive statistics. The results revealed that spices and aromatic herbs processing and commercialization are mainly female activities (80% of surveyed). The spices and aromatic herbs used in Benin are under several forms: fresh ones, dried ones, and powder obtained from one or a mixture of several spices and aromatic herbs. The products are commercialized through local markets and subregional markets (Nigeria, Ghana, Togo, Guinea). The appreciation of the quality of spices and aromatic herbs is based on quality attributes such as the aroma that must be marked and the physical aspect of fresh aromatic herbs. The spoilage of spices and aromatic herbs resulting in pungent taste, the attack by mould, and maggots, and the loss of aroma and weight of aromatic herbs during storage are the major problems claimed by the actors interviewed. Regarding the consumption, the spices and aromatic herbs are mainly used as flavouring and taste enhancer agents in all types of dishes. The current field investigation work also provided guidelines for the improvement of processing and storage practices of spices and aromatic herbs.
Keywords: Flavouring; taste enhancer; processing methods; consumption; quality; Benin